Surgery for Primary Cardiac Tumors in Children: Successful Management of Large Fibromas - Qian, Tao; Wu, Zhongshi; Yang, Yifeng; Xie, Li; Yin, Ni; Lu, Ting; Huang, Can; Yang, Hui (Frontiers in Cardiovascular Medicine, 2022)
Background Pediatric primary cardiac tumors (PCTs) are rare. Its clinical features and prognoses are not well defined. The management of asymptomatic patients with cardiac fibromas remains controversial. Objective We aimed to examine our experience in surgical resection of pediatric PCT, with specific focuses on the management of large fibromas. Methods This study included all the children who underwent surgical resection of PCT in our institution between December 2008 and June 2021. The last follow-up was performed between June 1st and August 26th, 2021. Kaplan–Meier method was used to estimate the postoperative survival, freedom from reoperation, event-free survival, and also related risk factors. The tumor volume and volume index (volume divided by body surface area) were measured for cardiac fibromas. Results Of the 39 patients with median operative age of 9.5 [interquartile range (IQR): 1.2–16.5] years, 35 (89.7%) had benign tumors (fibromas for 15, myxomas for 13, and others for 7). The length and volume of fibromas were independent of age and symptoms (Ps > 0.05). The fibroma volume index was negatively correlated with age (P = 0.039), with a mean value of 105 ± 70 ml/m2. Of the 15 patients with fibromas, 5 were asymptomatic, 4 received partial resection, 4 required transmural resection, and 4 presented postoperative left ventricular (LV) dysfunction (ejection fraction <50%). During the median follow-up period of 3.1 years and maximum of 12.5 years, adverse events included 2 early and 1 late death, 4 reoperations, 4 tumor recurrences, and 1 LV dysfunction lasting over one year. The 8-year survival, freedom from reoperation, and event-free survival rates were 90.4, 81.8, and 64.2%, respectively. Malignant tumor (P < 0.001) was associated with more adverse events. Transmural resection (P = 0.022) and larger tumor volume index than LV end-diastolic volume (P = 0.046) were risk factors for LV dysfunction following fibromas resection. Conclusion Pediatric surgery for PCT can be performed with low mortalities and few adverse events. The size of cardiac fibroma in children relatively decreases with the increase of age. Larger tumor volume index than LV end-diastolic volume index and transmural tumor resection predicts postoperative LV dysfunction.